ASEAN security multilateralism and the South China Sea - Loewen, Howard (The South China Sea Conflict after the Arbitration of July 12, 2016, 2020)
Since China and the Association of Southeast Asian Nations (ASEAN) members states have agreed on a Code of Conduct draft in June 2018 commentators have stated that ASEAN security multilateralism with regard to the South China Sea will finally be equipped with binding elements and thus more effective in solving cooperation problems. Against this background this paper disagrees and argues that different factors can explain the unsatisfactory balance of ASEAN security cooperation: Great Power politics, a culture of non-binding cooperation in ASEAN, the dominance of national interests and a tendency of ASEAN-states to hedge vis-à-vis great power competition.
CRIS-Team Scopus Importer:2020-10-09